2000
DOI: 10.1243/0954405001517874
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of material removal in ultrasonic drilling of engineering ceramics

Abstract: A new method for drilling holes in engineering ceramics by using a rotary ultrasonic tool has been developed. In this method, a drilling tool impregnated with abrasive particles is simultaneously rotated and vibrated. The mechanism of ultrasonic drilling is analysed using the concept of fracture mechanics and a new theoretical model of material removal rate (MRR) is proposed. According to this model, the material removal rate increases with increases of applied static load, amplitude of vibration and rotation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…2. Many abrasive machining models [17][18][19][20][21][22][23][24] began with an analysis of one abrasive particle. The models were then derived by summing up the effects of all active abrasive particles taking part in cutting.…”
Section: Approach To Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…2. Many abrasive machining models [17][18][19][20][21][22][23][24] began with an analysis of one abrasive particle. The models were then derived by summing up the effects of all active abrasive particles taking part in cutting.…”
Section: Approach To Model Developmentmentioning
confidence: 99%
“…Material removal mechanism in RUM of brittle materials has been mainly attributed to brittle fracture in the literature [14,[17][18][19][23][24]. The brittle fracture mechanism of materials has been discussed using indentation fracture mechanics [25][26][27][28].…”
Section: Volume Of Materials Removed By One Abrasive Particlementioning
confidence: 99%
“…drilling, grinding and electric discharge machining), rotary 1 ultrasonic machining (RUM) is an alternative machining method which is of particular interest for the machining of brittle and nonconductive materials as demonstrated in previous studies. 3,4 RUM is a hybrid machining process based on the combined material removal mechanisms of diamond grinding and ultrasonic machining resulting in higher material removal rates. The ultrasonically vibrating diamond-bonded tool is axially fed into the workpiece at a constant feed rate.…”
Section: Introductionmentioning
confidence: 99%
“…Pei et al [8] used rotary ultrasonic face machining first time and found the influence of the cutting depth, feed rate, and cutting tool on the machined surface quality and MRR. Zhang et al [9] established the material removal model based on the indentation theory for advanced ceramic and obtained the theoretical expression of MRR. This research verified the influence of static pressure, amplitude, spindle speed, and the grit size on MRR through experiments.…”
Section: Introductionmentioning
confidence: 99%
“…In previous study and literature review [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], it is found that there was main focus on machining ceramics and its related composite materials. The research work on rotary ultrasonic drilling of CFRP materials is rare especially on CFRP-T700.…”
Section: Introductionmentioning
confidence: 99%